The application of Fatwa in Malaysia and the contemporary challenges: the way forward - Chiroma, Magaji; Arifin, Mahamad; Ansari, Abdul Haseeb (Serials Publications, 2015)
Fatwa remains an Islamic legal verdict which has been issued by Muslim jurists or constituted authority established for that purpose. Nowadays, the application of fatwa alongside with the conventional law raises much concern about the threat of compromising its standard and values. Fatwa can be effectively utilized to streamline the Islamic principles and the contemporary developments. However, the application of fatwa does not mean “compromise” against its basic principles and objectives. Rather, the application always focuses on how fatwa can be used to enhance the application of Islamic law in line with the contemporary developments. In most of the modern Muslim countries, fatw do interact with the modern laws, and their interaction has generated a lot of controversies and conflicts as a result of the contemporary challenges which emanate basically from lack of effective bureaucracy, social and religious diversity, as well as legal pluralism. In view of this, the paper examines and analyzes the application of fatw in the contemporary Malaysian society with a view to identifying the challenges and proffering the possible solution thereto. Fatw, Application, Contemporary Challenges, The Way Forward